plz answer this question
Attachments:
![](https://hi-static.z-dn.net/files/dab/7f7af15d026c5b369e5a9a82085f9d10.png)
Answers
Answered by
1
Answer:
(a). f(x) = x^3-x^2-3x+3
x-1=0
x=1 , now if f(1) =0 the x-1 is a factor of f(x)
f(1)= 1^3 - 1^2- 3×1 +3
= 1-1-3+3
=0
therefore x-1 is a factor of f(x)
Answered by
3
Answer:
Now if f(1)=0 the x-1 is a factor of f(x)
Therefore (x-1) is a factor of f(x).
- hope it helps you...
- please mark it as a brainlist answer...
- also please rate thanks and follow me...
- stay home STAY SAFE...
Similar questions